The Learning Analysis Of Writing Poetry Using A Contextual Approach On Direct Object Onservation Technique For the PGSD Students - Susanti, Evi; Mugara, Ronny; Ramadhan Firdaus, Anugrah (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2023)
Learning to write poetry using a contextual approach to direct object observation techniques for PGSD students is an approach that could help elementary school students understand poetry writing. The purpose in this study in this study were third semester PGSD students at IKIP Siliwangi Cimahi. The method used in this study is quantitative research with the one-group pretest-posttest method. The population in this study was the PGSD students IKIP Siliwangi Â in Cimahi with a sample of 33 students. The instrument in this study was observation and a test. Based on the results of data analysis carried out with the average score of learning before using the contextual approach of direct object observation techniques and after using the contextual approach of direct object observation technique, it was revealed that there was a significant improvement as evidenced by the results of data analysis carried out with the average score of learning before using the contextual method direct object observation technique with the total score was 40.90 and after using contextual method direct object observation technique with the total score was 68.48.